MmNi5 and MmNi4.85Fe0.15 as Hydrogen Storage Medium - Johari, Anwar; Mohd. Yunus, Rosli; Noordin, Mohd. Suffian; Md. Ghazali, Mohd. Nazlee Faisal; Tuan Abdullah, Tuan Amran (Penerbit UTM Press, 2001)
The characteristics of MmNi5 and MmNi4.85Fe0.15 in storing hydrogen gas were examined in this study. The absorption capacity of the metal was monitored under the influence of temperature and pressure. Due to the limitation on its operating conditions, the range of the temperature chosen was from 298K to 323K while pressure was varied from 2 to 30 bar. Study conducted on MmNi5, showed that the amount of hydrogen absorbed was inversely proportional to the operating temperature. In the study of MnNi5 the maximum absorption was achieved at 298K and exhibited the plateau pressure of 10 bar. The hydrogen content was expressed as weight and the value was calculated to be at 1.20 wt%. As for MmNi5 at 313K abd 323K, the results are pointed at 0.9 wt% and 0.8 wt% whilst the plateau was encountedered at 20 and 24 bar, respectively. Study conducted on MmNi4.85Fe0.15 showed inconsistent findings with theory. After thorough examination, it was realized that the misbehavior of the sample was due to the insufficient agrresiveness activations method employed.